Business and Marketing Strategy Formulation for Caltara to Improve Company Performance in The Curtain Business - Marcel Saputra; Yos Sunitiyoso (AIBPM Publisher, 2021)
Caltara is one of the biggest curtain stores in Tasikmalaya, Indonesia, selling curtain fabric materials and other curtain accessories. The purpose of the research is to examine Caltara's existing business situations and develop a business and marketing strategy to enhance company performance. Based on the analysis, Caltara's target consumers are middle-class curtain stores. Caltara should position itself as a modern curtain business that delivers good-quality products at affordable prices, offer many product variations that keep up with the trends, and provide excellent service. Caltara should reduce the percentage of rejected products and waiting time, eliminate premium grade materials and product inconsistency, increase the knowledge of trendy motifs, provide excellent services, loyalty program, enhance marketing & advertising, variety of product and stock offered, distribute samples, create online sales application and provide delivery services. Blue ocean strategy, which includes the six path analysis, the four actions framework, and strategy canvas are utilized to identify opportunities for growth that have the potential for higher profits and faster growth for Caltara.